India : Note on Financial Accountability Systems of Selected State Level Power Sector Entities - World Bank (Washington, DC, 2014)
This study on financial accountability systems of selected state level power sector entities for India examines and highlights systemic issues of accounting, financial reporting, auditing, disclosure practices as well as capacity and policy gaps in state power sector entities. Sustainable recommendations have been developed to remove roadblocks and strengthen financial management, reporting and disclosure practices. Review and analysis of public material, financial statements, surveys and discussions with stakeholders have been used to understand operational practices and to report on the level of subsidies and return on investment. Finally, the study focuses on consensus building with stakeholders on key issues and solutions. The purpose of the recommendations is to advise the Bank and stakeholders, feeding into the Country Assistance Strategy (CAS), on the quality of corporate governance, reporting and management answerability for public investment ' in the power sector.